Recycled biodegradable polyester resin, recycled biodegradable polyester resin expanded sheet, and recycled biodegradable polyester resin expanded molding

The recycled biodegradable polyester resin addresses the challenge of recycling resin foam sheets and molded bodies by producing foam sheets and molded articles with excellent foaming properties, utilizing recycled materials and reducing environmental impact.

JP2025056425APending Publication Date: 2025-04-08SEKISUI PLASTICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023165888
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

There is a significant environmental and social burden due to the large-scale disposal of resin foam sheets and molded bodies, which are not easily recyclable, despite their excellent cushioning properties and moldability.

Method used

The development of a recycled biodegradable polyester resin that can be used to produce recycled biodegradable polyester resin foam sheets and molded articles with excellent foaming properties. This resin is made from recycled biodegradable polyester resin foam and has specific properties such as a slope of 0.30 (Pa·s) or more in a graph of uniaxial elongation viscosity, and a foaming ratio of 4 to 20 times.

Benefits of technology

The recycled biodegradable polyester resin enables the production of foam sheets and molded articles with superior foaming properties, even when using recycled materials, thus addressing the challenge of recycling and reducing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025056425000001_ABST
    Figure 2025056425000001_ABST
Patent Text Reader

Abstract

To provide a recycled biodegradable polyester resin capable of becoming a raw material of a recycled biodegradable polyester resin expanded sheet having excellent foaming property, a recycled biodegradable polyester resin expanded sheet having such recycled biodegradable polyester resin as a raw material, and a recycled biodegradable polyester resin expanded molding made by forming such recycled biodegradable polyester resin expanded sheet.SOLUTION: A recycled biodegradable polyester resin according to the embodiment of the present invention is a recycled biodegradable polyester resin that uses a biodegradable polyester resin foam as a recycled material, and in a graph where the logarithm of the strain ε is plotted on the horizontal axis and the logarithm of the elongation viscosity η (Pa s) is plotted on the vertical axis, obtained from the uniaxial elongation viscosity measurement at 160°C of the recycled biodegradable polyester resin, a slope a2 of the graph in the direction of increasing strain from the inflection point is 0.30 (Pa s) or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a recycled biodegradable polyester resin, a recycled biodegradable polyester resin foam sheet, and a recycled biodegradable polyester resin foam molded article. [Background technology]

[0002] 2. Description of the Related Art Resin foam sheets and resin foam molded articles are lightweight, have excellent cushioning properties, and can be easily molded into a variety of shapes, and therefore are used as the raw materials for various molded products, including packaging materials.

[0003] In recent years, resin foam sheets and resin foam molded articles are used in large quantities and then discarded in large quantities. This places a heavy burden on the environment and is a cause of various social problems such as global warming, resource depletion, and waste disposal. In response to this, foam sheets and foam molded articles using biodegradable polyester resins such as polylactic acid resins, which are biodegradable, have a small environmental impact, and can be produced relatively inexpensively, have been proposed (for example, Patent Document 1).

[0004] In general, in order to produce a foam sheet or a foam molded product from a resin, it is necessary that the melt tension of the raw material resin is relatively high. The same is true when producing a foam sheet or a foam molded product from a biodegradable polyester resin, and it is necessary that the melt tension of the raw material biodegradable polyester resin is relatively high. Therefore, when producing a foam sheet or a foam molded product from a biodegradable polyester resin, it has been proposed to use a modified biodegradable polyester resin that has been modified to provide a crosslinked structure or a branched structure in the molecule to increase the melt tension as the raw material biodegradable polyester resin (Patent Document 2).

[0005] On the other hand, like ordinary resin sheets and resin molded bodies, there is a strong social demand for recycling of resin foam sheets and resin foam molded bodies that are discarded in large quantities. Therefore, it can be said that the establishment of a recycling system for producing recycled biodegradable polyester resin foam sheets and recycled biodegradable polyester resin foam molded bodies having excellent foaming properties from recovered biodegradable polyester resin foam sheets and biodegradable polyester resin foam molded bodies will also become very important in the future society. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 6971947 [Patent Document 2] JP 2019-183098 A Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a recycled biodegradable polyester resin that can be used as a raw material for a recycled biodegradable polyester resin foam sheet having excellent foaming properties. Another object of the present invention is to provide a recycled biodegradable polyester resin foam sheet made from such a recycled biodegradable polyester resin. Another object of the present invention is to provide a recycled biodegradable polyester resin foam molded product obtained by molding such a recycled biodegradable polyester resin foam sheet. [Means for solving the problem]

[0008] [1] The recycled biodegradable polyester resin according to an embodiment of the present invention is a recycled biodegradable polyester resin made from biodegradable polyester resin foam as a recycled raw material, and in a graph obtained by uniaxial extensional viscosity measurement of the recycled biodegradable polyester resin at 160°C, the horizontal axis represents the logarithm of the amount of strain ε and the vertical axis represents the logarithm of the extensional viscosity η (Pa s), the slope a2 of the graph in the direction from the inflection point toward increasing amount of strain is 0.30 (Pa s) or more. [2] In the recycled biodegradable polyester resin described in [1] above, the biodegradable polyester resin foam may be produced by melt-kneading a resin composition containing a biodegradable polyester resin in an extruder and extruding and foaming it. [3] In the recycled biodegradable polyester resin described in [2] above, in a graph in which the horizontal axis represents the logarithm of the amount of strain ε and the vertical axis represents the logarithm of the extensional viscosity η (Pa·s), obtained by uniaxial extensional viscosity measurement of the biodegradable polyester resin at 160°C, the ratio (a2 / a1) of the slope a2 (Pa·s) of the graph in the direction in which the amount of strain increases from the inflection point may be 0.10 or more. [4] In the recycled biodegradable polyester resin according to the above [2] or [3], the biodegradable polyester resin may be a polylactic acid resin (P). [5] In the recycled biodegradable polyester resin described in [4] above, the polylactic acid resin (P) may be a modified polylactic acid resin. [6] In the recycled biodegradable polyester resin according to any one of [1] to [5] above, the biodegradable polyester resin may be obtained by melt-kneading a raw material composition containing the biodegradable polyester resin foam in an extruder, and pelletizing the extruded mixture. [7] In the recycled biodegradable polyester resin according to any one of the above items [1] to [5], the recycled biodegradable polyester resin may be the biodegradable polyester resin foam. [8] In the recycled biodegradable polyester resin according to any one of [1] to [7] above, the Z-average molecular weight (M Z ) may be 300,000 or more. [9] In the recycled biodegradable polyester resin according to any one of [1] to [8] above, the recycled biodegradable polyester resin may have an MFR of 15 g / 10 min or less.

[10] In the recycled biodegradable polyester resin according to any one of [1] to [9] above, the recycled biodegradable polyester resin may have a melt tension of 1 cN or more at 190°C.

[11] A recycled biodegradable polyester resin foam sheet according to an embodiment of the present invention is obtained by foaming a recycled resin composition containing the recycled biodegradable polyester resin described in any one of [1] to

[10] above.

[12] In the recycled biodegradable polyester resin foam sheet according to the above item

[11] , in a graph obtained by uniaxial extensional viscosity measurement of the recycled biodegradable polyester resin foam sheet at 160°C, the horizontal axis represents the logarithm of the amount of strain ε and the vertical axis represents the logarithm of the extensional viscosity η (Pa s), the slope a3 of the graph in the direction from the inflection point toward an increase in the amount of strain may be 0.30 (Pa s) or more.

[13] The recycled biodegradable polyester resin foam sheet according to the above

[11] or

[12] may have a thickness of 0.5 mm to 7 mm.

[14] The recycled biodegradable polyester resin foam sheet according to any one of

[11] to

[13] above, wherein the basis weight is 50 g / m 2 ~600g / m 2 may be also possible.

[15] In the recycled biodegradable polyester resin foam sheet according to any one of the above

[11] to

[14] , the foaming ratio may be 4 to 20 times.

[16] In the recycled biodegradable polyester resin foam sheet according to any one of

[11] to

[15] above, an open cell ratio may be 50% or less.

[17] A recycled biodegradable polyester resin foam molding according to an embodiment of the present invention is obtained by molding a recycled biodegradable polyester resin foam sheet according to any one of the above

[11] to

[16] . Effect of the Invention

[0009] According to an embodiment of the present invention, it is possible to provide a recycled biodegradable polyester resin that can be used as a raw material for a recycled biodegradable polyester resin foam sheet having excellent foaming properties. It is also possible to provide a recycled biodegradable polyester resin foam sheet made from such a recycled biodegradable polyester resin. Furthermore, it is also possible to provide a recycled biodegradable polyester resin foam molding obtained by molding such a recycled biodegradable polyester resin foam sheet. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a graph showing an example of a graph in which the horizontal axis represents the logarithm of the strain amount ε (unit: dimensionless) and the vertical axis represents the logarithm of the extensional viscosity η (unit: Pa s) obtained by uniaxial extensional viscosity measurement at 160°C of a recycled biodegradable polyester resin according to an embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic diagram showing one preferred configuration of an extruder used in an embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic diagram showing a preferred configuration of a production apparatus suitable for producing a foamed sheet in an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0012] The "recycled biodegradable polyester resin" in the present invention means a recycled biodegradable polyester resin made from the "biodegradable polyester resin foam" in the present invention (e.g., a biodegradable polyester resin foam sheet or a biodegradable polyester resin foam molding) as a recycled raw material.

[0013] The "recycled biodegradable polyester resin foam sheet" in the present invention means a foam sheet obtained by foaming a recycled resin composition containing the "recycled biodegradable polyester resin" in the present invention.

[0014] The "recycled biodegradable polyester resin foam molded article" in the present invention means a foam molded article obtained by molding the "recycled biodegradable polyester resin foam sheet" in the present invention.

[0015] In this specification, "polylactic acid resin" means "modified polylactic acid resin" or "unmodified polylactic acid resin". In this specification, when "polylactic acid resin (P)" is not described and "polylactic acid resin" is simply described, it means unmodified polylactic acid resin. Here, "unmodified polylactic acid resin" means polylactic acid resin that has not been modified, typically a polylactic acid resin that is generally available, and not a modified polylactic acid resin that has been modified.

[0016] In this specification, the term "substantially 100% by mass" means that the presence of a trace amount (for example, less than 1% by mass) of unintentionally mixed impurities may be ignored.

[0017] ≪≪1. Recycled biodegradable polyester resin≫≫ The recycled biodegradable polyester resin according to the embodiment of the present invention uses a biodegradable polyester resin foam as a recycled raw material. The biodegradable polyester resin foam may be of one type or of two or more types.

[0018] As the biodegradable polyester resin foam as a recycled raw material, any appropriate foam may be adopted as long as the effects of the present invention are not impaired. Examples of such biodegradable polyester resin foam include a biodegradable polyester resin foam sheet and a biodegradable polyester resin foam molded product obtained by molding the biodegradable polyester resin foam sheet.

[0019] A representative example of the biodegradable polyester resin foam as a recycled raw material is a recovered biodegradable polyester resin foam. Such a biodegradable polyester resin foam may be a non-recycled biodegradable polyester resin foam, or may be a recycled biodegradable polyester resin foam as long as the effect of the present invention is not impaired. A representative example of such a biodegradable polyester resin foam is a biodegradable polyester resin foam obtained by melt-kneading a resin composition containing a biodegradable polyester resin in an extruder and extruding and foaming it. The above-mentioned "biodegradable polyester resin" may be a recycled biodegradable polyester resin, a non-recycled biodegradable polyester resin, or a mixture thereof, but is typically a non-recycled biodegradable polyester resin.

[0020] The biodegradable polyester resin foam as a recycled raw material may be used in any appropriate form depending on the type and scale of the device used to produce the recycled biodegradable polyester resin. The form of such a biodegradable polyester resin foam may be, for example, the form as it is, a pulverized product obtained by pulverizing the pulverized product, a pellet made from the pulverized product, or a pulverized product of the pellets.

[0021] In the recycled biodegradable polyester resin according to the embodiment of the present invention, in a graph in which the logarithm of the strain amount ε (unit: dimensionless) obtained by uniaxial extensional viscosity measurement at 160 ° C. is plotted on the horizontal axis and the logarithm of the extensional viscosity η (unit: Pa · s) is plotted on the vertical axis, the slope a2 of the graph in the direction from the inflection point toward an increase in the strain amount is typically 0.30 (Pa · s) or more, preferably 0.35 (Pa · s) or more, more preferably 0.40 (Pa · s) or more, and particularly preferably 0.45 (Pa · s) or more. The upper limit of the slope a1 of the graph is preferably 4.00 (Pa · s) or less, more preferably 3.00 (Pa · s) or less, even more preferably 2.50 (Pa · s) or less, particularly preferably 2.00 (Pa · s) or less, and most preferably 1.50 (Pa · s) or less, in order to further exhibit the effects of the present invention. If the slope a2 of the graph is within the above range, the recycled biodegradable polyester resin according to the embodiment of the present invention can have excellent strain hardening properties. In general, the strain hardening properties of polyester resins may be reduced by applying a thermal history using an extruder or the like, and this reduction in strain hardening properties leads to reduced foaming properties when the polyester resin is foamed into a foamed sheet. The recycled biodegradable polyester resin according to the embodiment of the present invention has excellent strain hardening properties even when it is subjected to a thermal history using an extruder or the like, and therefore can be used as a raw material for a recycled biodegradable polyester resin foamed sheet having excellent foaming properties.

[0022] FIG. 1 shows an example of a graph in which the horizontal axis represents the logarithm of the strain amount ε (unit: dimensionless) and the vertical axis represents the logarithm of the extensional viscosity η (unit: Pa·s) obtained by uniaxial extensional viscosity measurement at 160°C for the recycled biodegradable polyester resin according to an embodiment of the present invention. In FIG. 1, the horizontal axis represents the logarithm of the strain amount ε (unit: dimensionless), and the vertical axis represents the logarithm of the extensional viscosity η (unit: Pa·s). In FIG. 1, V is an inflection point. In the present invention, the slope a2 of the graph in the direction from the inflection point to the direction in which the strain amount increases is the slope of the straight line obtained by linear approximation by the least squares method for the curve from the inflection point V to the point where the extensional viscosity η is the maximum value in the direction in which the strain amount increases, when explained using FIG. 1 as an example. Note that in the recycled biodegradable polyester resin, the slope of the graph in the direction in which the strain amount decreases from the inflection point may be a negative value. The same applies to the gradients a1 and a3 of the graph in the direction in which the amount of distortion increases from the inflection point described later.

[0023] In the recycled biodegradable polyester resin according to an embodiment of the present invention, the ratio (a2 / a1) of the slope a2 (Pa·s) of the above graph to the slope a1 (Pa·s) of the graph in the direction from the inflection point toward increasing strain, in a graph in which the horizontal axis represents the logarithm of the strain amount ε (unit: dimensionless) and the vertical axis represents the logarithm of the extensional viscosity η (Pa·s), both of which are obtained by uniaxial extensional viscosity measurement at 160°C of the biodegradable polyester resin that is the raw material of the biodegradable polyester resin foam, which is the recycled raw material, is preferably 0.10 or more, more preferably 0.10 to 1.50, even more preferably 0.15 to 1.40, particularly preferably 0.20 to 1.35, and most preferably 0.25 to 1.30. When the ratio (a2 / a1) is within the above range, the recycled biodegradable polyester resin according to an embodiment of the present invention can be used as a raw material for a recycled biodegradable polyester resin foam sheet having better foaming properties, since the deterioration of strain hardening caused by the biodegradable polyester resin, which is the raw material for the biodegradable polyester resin foam, which is the recycled raw material, is suppressed even when the recycled biodegradable polyester resin is subjected to a thermal history using an extruder or the like.

[0024] The recycled biodegradable polyester resin according to the embodiment of the present invention has an MFR of preferably 15 g / 10 min or less, more preferably 0.2 g / 10 min to 15 g / 10 min or less, even more preferably 0.5 g / 10 min to 13 g / 10 min or less, particularly preferably 1.0 g / 10 min to 10 g / 10 min or less, and most preferably 1.0 g / 10 min to 8.0 g / 10 min. If the MFR is within the above range, the recycled biodegradable polyester resin according to the embodiment of the present invention can exhibit appropriate fluidity when thermally melted, have better strain hardening properties, and can be a raw material for a recycled biodegradable polyester resin foam sheet having better foaming properties.

[0025] The recycled biodegradable polyester resin according to the embodiment of the present invention has a melt tension at 190°C of preferably 1 cN or more, more preferably 1 cN to 100 cN, even more preferably 1 cN to 80 cN, particularly preferably 1 cN to 70 cN, and most preferably 1 cN to 60 cN. If the melt tension is within the above range, the recycled biodegradable polyester resin according to the embodiment of the present invention can be used as a raw material for a recycled biodegradable polyester resin foam sheet having better foaming properties. In particular, even if the melt tension is low, the recycled biodegradable polyester resin according to the embodiment of the present invention has better strain hardening properties and can be used as a raw material for a recycled biodegradable polyester resin foam sheet having better foaming properties.

[0026] The recycled biodegradable polyester resin according to an embodiment of the present invention has a Z-average molecular weight (M Z The Z-average molecular weight (M) is preferably 300,000 or more, more preferably 400,000 or more, further preferably 500,000 or more, and particularly preferably 600,000 or more. Z The upper limit of the Z-average molecular weight (M) is preferably 1,800,000 or less, more preferably 1,600,000 or less, further preferably 1,500,000 or less, and particularly preferably 1,300,000 or less. Z) is an average molecular weight that emphasizes the contribution of high molecular weight components. Therefore, the above Z-average molecular weight (M Z If the Z-average molecular weight (M) is within the above range, it means that the recycled biodegradable polyester resin according to the embodiment of the present invention has a significant amount of high molecular weight components remaining even when subjected to a heat history by an extruder or the like. Since the high molecular weight components remain significantly in this manner, the recycled biodegradable polyester resin according to the embodiment of the present invention has better strain hardening properties and can be used as a raw material for a recycled biodegradable polyester resin foam sheet having better foaming properties. Z ) is too small, the amount of high molecular weight components remaining in the recycled biodegradable polyester resin according to the embodiment of the present invention will be small, which may result in a decrease in strain hardening properties, and the recycled biodegradable polyester resin may not be able to serve as a raw material for a recycled biodegradable polyester resin foam sheet having excellent foaming properties.

[0027] The recycled biodegradable polyester resin according to an embodiment of the present invention has a number average molecular weight (Mn) of preferably 10,000 to 150,000, more preferably 20,000 to 130,000, further preferably 30,000 to 120,000, and particularly preferably 40,000 to 110,000.

[0028] The recycled biodegradable polyester resin according to an embodiment of the present invention has a weight average molecular weight (Mw) of preferably 100,000 to 1,000,000, more preferably 130,000 to 500,000, further preferably 150,000 to 400,000, and particularly preferably 200,000 to 350,000.

[0029] The recycled biodegradable polyester resin according to the embodiment of the present invention has a melting point of preferably 130°C to 175°C, more preferably 135°C to 170°C, and further preferably 138°C to 168°C.

[0030] The recycled biodegradable polyester resin according to the embodiment of the present invention has a crystallization temperature of preferably 70°C to 110°C, more preferably 75°C to 105°C, and further preferably 78°C to 103°C.

[0031] 1-1. First embodiment of recycled biodegradable polyester resin The recycled biodegradable polyester resin according to the first embodiment of the present invention is produced by melt-kneading a raw material composition containing a biodegradable polyester resin foam as a recycled raw material in an extruder, and pelletizing the extruded mixture. The recycled biodegradable polyester resin according to this embodiment can be typically produced by a method including a kneading step of melt-kneading a raw material composition containing a biodegradable polyester resin foam as a recycled raw material in an extruder, and a pelletizing step of pelletizing the mixture extruded from the extruder.

[0032] When producing the recycled biodegradable polyester resin according to an embodiment of the present invention, any appropriate other steps may be included in addition to the kneading step and the pelletizing step, as long as the effects of the present invention are not impaired.

[0033] The recycled biodegradable polyester resin according to the embodiment of the present invention preferably further includes a drying step for adjusting the moisture content of the pellets obtained in the pelletizing step. The moisture content after adjustment in the drying step is preferably 0.30% by mass or less, more preferably 0.25% by mass or less, even more preferably 0.20% by mass or less, even more preferably 0.15% by mass or less, particularly preferably 0.10% by mass or less, and most preferably 0.05% by mass or less. The lower limit of the moisture content after adjustment in this drying step is the lower the better, and ideally 0% by mass. By strictly adjusting the moisture content of the pellets within the above range in the drying step, the obtained recycled biodegradable polyester resin can be given excellent strain hardening properties. This makes it possible to provide a recycled biodegradable polyester resin that can be used as a raw material for a recycled biodegradable polyester resin foam sheet having excellent foaming properties.

[0034] When producing the recycled biodegradable polyester resin according to an embodiment of the present invention, in order to efficiently proceed with the pelletizing process, a cooling process may be included after the kneading process and before the pelletizing process, in which the kneaded material extruded from the extruder is cooled.

[0035] It was found that the moisture content of the pellets obtained in the pelletizing process tends to be high when the cooling process is included. As a result of examining this tendency, it was presumed that the temperature of the high-temperature kneaded material extruded from the extruder can drop rapidly in the cooling process, which makes it easier for moisture to be taken up by the kneaded material. In fact, when a recycled biodegradable polyester resin foam sheet was produced using a recycled biodegradable polyester resin obtained using pellets with a high moisture content obtained when the cooling process is included, it was found that the foaming properties were poor. However, it was found that by adopting the above-mentioned drying process, a recycled biodegradable polyester resin that can be used as a raw material for a recycled biodegradable polyester resin foam sheet having excellent foaming properties can be provided even when the cooling process is included.

[0036] The recycled biodegradable polyester resin according to the embodiment of the present invention can be produced using any suitable production apparatus as long as the effects of the present invention are not impaired. In order to further demonstrate the effects of the present invention, the recycled biodegradable polyester resin according to the embodiment of the present invention can be produced using, for example, a production apparatus as shown in FIG.

[0037] As shown in FIG. 2, typically, a raw material composition containing a biodegradable polyester resin foam as a recycled raw material (which may be a pulverized product of the foam, or pellets made from the pulverized product, or a pulverized product of the pellets, as necessary) is fed into a hopper 11, melt-kneaded by a twin-screw extruder 30, the strand-shaped kneaded product extruded from a strand die 3 is cooled by a cooling device 6, and then pelletized by a pelletizer 4 and dried by a drying device 5, thereby obtaining a recycled biodegradable polyester resin according to an embodiment of the present invention in the form of pellets.

[0038] <1-1-a. Mixing process> In the kneading step, a raw material composition containing a biodegradable polyester resin foam, which is a recycled raw material, is melt-kneaded in an extruder.

[0039] The biodegradable polyester resin foam, which is a recycled raw material, will be described in detail later.

[0040] The raw material composition contains a biodegradable polyester resin foam that is a recycled raw material. The raw material composition may contain any appropriate component other than the biodegradable polyester resin foam as long as the effect of the present invention is not impaired.

[0041] The content of the biodegradable polyester resin foam in the raw material composition is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, even more preferably 90% by mass to 100% by mass, and particularly preferably 95% by mass to 100% by mass, in order to further exert the effects of the present invention.

[0042] As the extruder, any appropriate extruder may be used as long as the effects of the present invention are not impaired. In terms of being able to more effectively exhibit the effects of the present invention, the extruder is preferably a twin-screw extruder.

[0043] The twin-screw extruder may be equipped with a strand die or a T-die.

[0044] The temperature conditions for melt kneading may vary depending on the size of extrusion, the discharge amount, etc., and any appropriate conditions may be adopted as long as the effects of the present invention are not impaired. For example, the temperature of the raw material feed section is preferably set to 100°C to 200°C.

[0045] The rotation speed of the extruder may vary depending on the size of the extrusion, the discharge amount, etc., and any appropriate condition may be adopted within a range that does not impair the effects of the present invention. Such a rotation speed is, for example, preferably 20 rpm to 800 rpm.

[0046] <1-1-b. Cooling process> In the cooling step, any appropriate cooling method may be adopted as long as the effects of the present invention are not impaired. Examples of such cooling methods include a method using a cooling device, and a representative example is a method in which the strand discharged from the strand die is water-cooled, specifically, a method in which the strand discharged from the strand die is water-cooled by introducing it into a water tank.

[0047] The cooling temperature is preferably 70° C. or lower, more preferably 60° C. or lower, even more preferably 50° C. or lower, particularly preferably 40° C. or lower, and most preferably 35° C. or lower. There are no particular limitations on the lower limit of the cooling temperature, but taking into consideration the cost of cooling and the like, it is practically preferably 5° C. or higher, more preferably 10° C. or higher.

[0048] <1-1-c. Pelletizing process> In the pelletizing step, the kneaded material extruded from the extruder in the kneading step is pelletized.

[0049] As the pelletizing method in the pelletizing step, any suitable pelletizing method can be adopted as long as it can pelletize the kneaded material extruded from the extruder in the kneading step without impairing the effects of the present invention. A typical pelletizing method is to cut the strand-shaped or sheet-shaped kneaded material extruded from the extruder in the kneading step with a pelletizer to prepare pellets. In order to efficiently proceed with the pelletizing step, a cooling step may be included after the kneading step and before the pelletizing step.

[0050] As the pelletizer, any appropriate pelletizer can be adopted as long as it does not impair the effects of the present invention.

[0051] The extruder in the kneading step may be equipped with a pelletizing die (hot cut die). In this case, the kneaded material is pelletized immediately after being extruded, and the pelletization in the pelletizing die constitutes the pelletizing step.

[0052] <1-1-d. Drying process> In the drying step, the moisture content of the pellets obtained in the pelletizing step is adjusted. The moisture content after the adjustment in the drying step is preferably 0.30% by mass or less, more preferably 0.25% by mass or less, even more preferably 0.20% by mass or less, even more preferably 0.15% by mass or less, particularly preferably 0.10% by mass or less, and most preferably 0.05% by mass or less. The lower limit of the moisture content after the adjustment in this drying step is the lower the better, and ideally 0% by mass. By strictly adjusting the moisture content of the pellets in the drying step to within the above range, the obtained recycled biodegradable polyester resin can be given excellent strain hardening properties. This makes it possible to provide a recycled biodegradable polyester resin that can be used as a raw material for a recycled biodegradable polyester resin foam sheet having excellent foaming properties.

[0053] As a method for strictly adjusting the moisture content of the pellets to within a predetermined range in the drying process, any appropriate method may be adopted as long as it does not impair the effects of the present invention. For example, such a method includes a method of drying the pellets using a dryer such as a dehumidifying dryer, a vacuum dryer, or a hot air dryer. It is a preferred embodiment that the pellets thoroughly dried in a dryer or the like are directly introduced into the next process (without being exposed to a moisture-containing environment). It is also a preferred embodiment that the pellets thoroughly dried in a dryer or the like are immediately sealed in an aluminum bag after drying, and the bag is opened just before being introduced into the next process.

[0054] 1-2. Second embodiment of recycled biodegradable polyester resin The recycled biodegradable polyester resin according to the second embodiment of the present invention is a biodegradable polyester resin foam that is a recycled raw material. The recycled biodegradable polyester resin according to this embodiment is typically the biodegradable polyester resin foam itself that is a recycled raw material, and is typically a pulverized product.

[0055] The recycled biodegradable polyester resin according to the second embodiment of the present invention is different from the recycled biodegradable polyester resin according to the first embodiment of the present invention described above, and is not produced by melt-kneading a biodegradable polyester resin foam, which is a recycled raw material, in an extruder and pelletizing the kneaded material extruded from the extruder.

[0056] <1-3. Biodegradable polyester resin foam as a recycled material> A representative example of the biodegradable polyester resin foam as a recycled raw material is a biodegradable polyester resin foam obtained by melt-kneading and extrusion-foaming a resin composition containing a biodegradable polyester resin in an extruder. Therefore, a representative embodiment of the biodegradable polyester resin foam is a biodegradable polyester resin foam sheet obtained by melt-kneading and extrusion-foaming a resin composition containing a biodegradable polyester resin in an extruder, or a biodegradable polyester resin foam molded product obtained by molding the foam sheet.

[0057] The biodegradable polyester resin foam has an open cell ratio of preferably 50% or less, more preferably 40% or less, even more preferably 30% or less, still more preferably 20% or less, and particularly preferably 15% or less.

[0058] The biodegradable polyester resin foam has an average cell diameter of preferably 100 μm to 850 μm, more preferably 150 μm to 800 μm, and further preferably 200 μm to 750 μm.

[0059] The expansion ratio of the biodegradable polyester resin foam is preferably 4 to 20 times, more preferably 4 to 15 times, further preferably 4 to 12 times, and particularly preferably 4 to 10 times.

[0060] <1-3-a. Resin composition> One embodiment of the biodegradable polyester resin foam is a biodegradable polyester resin foam sheet obtained by melt-kneading a resin composition containing a biodegradable polyester resin in an extruder and extrusion-foaming it, or a biodegradable polyester resin foam molded article obtained by molding the foam sheet.

[0061] The content of the biodegradable polyester resin in the resin composition is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and even more preferably 90% by mass to 100% by mass, in order to achieve the effects of the present invention.

[0062] [Biodegradable polyester resin as a raw material for biodegradable polyester resin foam] As the biodegradable polyester resin as a raw material of the biodegradable polyester resin foam, any appropriate biodegradable polyester resin may be adopted as long as it does not impair the effects of the present invention. The biodegradable polyester resin may be one type or two or more types.

[0063] The biodegradable polyester resin as a raw material for the biodegradable polyester resin foam has an MFR of preferably 10.0 g / 10 min or less, more preferably 0.2 g / 10 min to 6.0 g / 10 min, even more preferably 0.3 g / 10 min to 5.0 g / 10 min, particularly preferably 0.5 g / 10 min to 4.0 g / 10 min, and most preferably 0.8 g / 10 min to 3.0 g / 10 min, in order to further exert the effects of the present invention. By having the MFR of the biodegradable polyester resin within the above range, it is possible to exert an appropriate fluidity during heat melting, and the effects of the present invention can be further exerted.

[0064] The biodegradable polyester resin used as a raw material for the biodegradable polyester resin foam preferably has a melt tension at 190°C of 18 cN or more, more preferably 20 cN to 100 cN, even more preferably 30 cN to 80 cN, particularly preferably 40 cN to 70 cN, and most preferably more than 40 cN to 60 cN or less, in order to better exhibit the effects of the present invention.

[0065] The biodegradable polyester resin used as the raw material for the biodegradable polyester resin foam has a Z-average molecular weight (M Z The Z-average molecular weight (M) is preferably 500,000 or more, more preferably 700,000 or more, further preferably 900,000 or more, and particularly preferably 1,000,000 or more. Z ) is preferably 1,500,000 or less, more preferably 1,400,000 or less, even more preferably 1,300,000 or less, and particularly preferably 1,200,000 or less.

[0066] The biodegradable polyester resin used as a raw material for the biodegradable polyester resin foam preferably has a number average molecular weight (Mn) of 30,000 to 180,000, more preferably 40,000 to 150,000, even more preferably 50,000 to 130,000, and particularly preferably 60,000 to 100,000, in order to better exhibit the effects of the present invention.

[0067] The biodegradable polyester resin used as a raw material for the biodegradable polyester resin foam preferably has a weight average molecular weight (Mw) of 100,000 to 700,000, more preferably 130,000 to 550,000, even more preferably 150,000 to 500,000, and particularly preferably 200,000 to 450,000, in order to further exert the effects of the present invention.

[0068] The biodegradable polyester resin used as a raw material for the biodegradable polyester resin foam preferably has a melting point of 130°C to 175°C, more preferably 135°C to 170°C, and even more preferably 138°C to 168°C, in order to better exhibit the effects of the present invention.

[0069] The biodegradable polyester resin used as a raw material for the biodegradable polyester resin foam preferably has a crystallization temperature of 70°C to 110°C, more preferably 75°C to 105°C, and even more preferably 78°C to 103°C, in order to better exhibit the effects of the present invention.

[0070] In terms of being able to more effectively exhibit the effects of the present invention, the moisture content of the biodegradable polyester resin immediately before being fed into the extruder is preferably 0.30% by mass or less, more preferably 0.25% by mass or less, even more preferably 0.20% by mass or less, particularly preferably 0.17% by mass or less, and most preferably 0.15% by mass or less. The lower limit of the moisture content is preferably as low as possible, and is ideally 0% by mass. The moisture content immediately before being fed into the extruder can be measured, for example, by a Karl Fischer moisture content meter. In terms of being able to more effectively exhibit the effects of the present invention, the biodegradable polyester resin as a raw material for the biodegradable polyester resin foam has a graph in which the horizontal axis is the logarithm of the strain amount ε (unit: dimensionless) obtained by uniaxial extensional viscosity measurement at 160 ° C., and the vertical axis is the logarithm of the extensional viscosity η (Pa · s), and the slope a1 (Pa · s) of the graph in the direction from the inflection point toward an increase in the strain amount is preferably 0.50 (Pa · s) or more, more preferably 1.00 (Pa · s) or more, and particularly preferably 1.50 (Pa · s) or more. In terms of being able to more effectively exhibit the effects of the present invention, the upper limit of the slope a1 of the graph is preferably 5.00 (Pa · s) or less, more preferably 4.00 (Pa · s) or less, even more preferably 3.00 (Pa · s) or less, particularly preferably 2.70 (Pa · s) or less, and most preferably 2.50 (Pa · s) or less.

[0071] The biodegradable polyester resin is preferably a polylactic acid resin (P) in that the effects of the present invention can be more effectively exhibited.

[0072] The polylactic acid resin (P) may be a modified polylactic acid resin, an unmodified polylactic acid resin, or a mixture thereof.

[0073] The polylactic acid resin (P) typically contains a modified polylactic acid resin as a main component. The content of the modified polylactic acid resin in the polylactic acid resin (P) is preferably more than 50% by mass, more preferably 70% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, and most preferably substantially 100% by mass.

[0074] The modified polylactic acid resin is preferably obtained by melt-kneading a polylactic acid resin composition containing a polylactic acid resin and a modifier in an extruder.

[0075] The polylactic acid resin may be a homopolymer of lactic acid or a copolymer of lactic acid and other monomers, such as aliphatic hydroxycarboxylic acids other than lactic acid, aliphatic polyhydric alcohols, aliphatic polycarboxylic acids, and polyfunctional polysaccharides.

[0076] The lactic acid constituting the polylactic acid resin may be either the L-form or the D-form, or may be both the L-form and the D-form. That is, the polylactic acid resin, which is a homopolymer of lactic acid, may be any of poly(L-lactic acid) resin, poly(D-lactic acid) resin, and poly(DL-lactic acid) resin.

[0077] Examples of hydroxycarboxylic acids other than lactic acid include glycolic acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 4-hydroxyvaleric acid, 5-hydroxyvaleric acid, and 6-hydroxycaproic acid.

[0078] Examples of the aliphatic polyhydric alcohol include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,3-butanediol, 1,4-butanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, neopentyl glycol, tetramethylene glycol, and 1,4-cyclohexanedimethanol.

[0079] Examples of the aliphatic polycarboxylic acid include oxalic acid, succinic acid, malonic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, undecanedioic acid, and dodecanedioic acid. The aliphatic polycarboxylic acid may be an acid anhydride.

[0080] Examples of polyfunctional polysaccharides include cellulose, cellulose nitrate, methylcellulose, ethylcellulose, celluloid, viscose rayon, regenerated cellulose, cellophane, cupra, cuprammonium rayon, cuprophane, Bemberg, hemicellulol, starch, acropectin, dextrin, dextran, glycogen, pectin, chitin, chitosan, gum arabic, guar gum, locust bean gum, and acacia gum.

[0081] In the polylactic acid resin, the content of structural portions derived from lactic acid (L- and D-form) in the molecule is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, particularly preferably 80% by mass or more, and most preferably 90% by mass or more.

[0082] At least a part of the polylactic acid resin may be recycled.

[0083] The modifier exerts the effect of increasing the molecular weight of the polylactic acid resin and imparting a cross-linked structure or a long-chain branched structure to the molecular structure of the polylactic acid resin.

[0084] The modifier may be of only one type, or of two or more types.

[0085] To increase the molecular weight of polylactic acid resin, a chain extender such as carbodiimide can be used as a modifier. In the modification using a chain extender, a compound having one or more functional groups capable of undergoing a condensation reaction with a hydroxyl group or a carboxyl group present in the molecular structure of polylactic acid resin, such as an acrylic organic compound, an epoxy organic compound, or an isocyanate organic compound, can be used. That is, the molecular weight of polylactic acid resin can be increased by using a chain extender such as carbodiimide to bond an acrylic organic compound, an epoxy organic compound, an isocyanate organic compound, or the like to the polylactic acid resin.

[0086] In order to provide a crosslinked structure or a long-chain branched structure in the molecular structure of polylactic acid resin, for example, a radical initiator can be used as a modifier. In this case, polylactic acid resins are reacted with each other using a radical initiator having appropriate reactivity. When polylactic acid resins are reacted with each other using a radical initiator having appropriate reactivity, for example, the decomposition starting point of the polylactic acid resin in the extruder is attacked by the free radicals generated by the radical initiator, and the site becomes a crosslinked point (branching point) and can be stabilized. By performing such modification, the thermal stability of the polylactic acid resin is increased and the molecular weight is less likely to be reduced when passing through the extruder.

[0087] Examples of the radical initiator include organic peroxides, azo compounds, and halogen molecules, with organic peroxides being preferred.

[0088] Examples of organic peroxides include peroxy esters, hydroperoxides, dialkyl peroxides, diacyl peroxides, peroxydicarbonates, peroxyketals, and ketone peroxides.

[0089] Examples of peroxy esters include t-butylperoxy 2-ethylhexyl carbonate, t-hexylperoxy isopropyl monocarbonate, t-hexylperoxybenzoate, t-butylperoxybenzoate, t-butylperoxylaurate, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxyacetate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, and t-butylperoxyisopropyl monocarbonate.

[0090] Examples of hydroperoxides include permethane hydroperoxide, diisopropylbenzene hydroperoxide, cumene hydroperoxide, and t-butyl hydroperoxide.

[0091] Examples of dialkyl peroxides include dicumyl peroxide, di-t-butyl peroxide, and 2,5-dimethyl-2,5-di(t-butylperoxy)-hexyne-3.

[0092] Examples of diacyl peroxides include dibenzoyl peroxide, di(4-methylbenzoyl) peroxide, and di(3-methylbenzoyl) peroxide.

[0093] Examples of peroxydicarbonates include di(2-ethylhexyl) peroxydicarbonate and diisopropyl peroxydicarbonate.

[0094] Examples of peroxyketals include 1,1-di-t-butylperoxy-3,3,5-trimethylcyclohexane, 1,1-di-t-butylperoxycyclohexane, 2,2-di(t-butylperoxy)-butane, n-butyl 4,4-di-(t-butylperoxy)valerate, and 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane.

[0095] Examples of the ketone peroxide include methyl ethyl ketone peroxide and acetylacetone peroxide.

[0096] In the modification with organic peroxide, there is a risk that the modified polylactic acid resin may be mixed with components having an excessively large molecular weight that may gel when thermally melted, or that odor problems may occur due to decomposition residues of the organic peroxide. The organic peroxide is preferably a peroxyester, in that it can suppress the occurrence of such problems and can easily modify the polylactic acid resin to a state suitable for foaming. Among peroxyesters, peroxycarbonate-based organic peroxides such as peroxymonocarbonate and peroxydicarbonate are preferred. Furthermore, among peroxycarbonate-based organic peroxides, peroxymonocarbonate-based organic peroxides are preferred, and t-butylperoxyisopropylmonocarbonate is more preferred.

[0097] The amount of organic peroxide used depends on the molecular weight, etc., but in order to more effectively exhibit the effects of the present invention, it is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, and even more preferably 0.3 parts by mass or more, relative to 100 parts by mass of polylactic acid resin. The upper limit of the amount of organic peroxide used is preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less, and even more preferably 1.0 part by mass or less.

[0098] The polylactic acid resin composition containing the polylactic acid resin and the modifier may contain any appropriate other components than the polylactic acid resin and the modifier within a range that does not impair the effects of the present invention. The total content of the polylactic acid resin and the modifier in the polylactic acid resin composition containing the polylactic acid resin and the modifier is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, even more preferably 90% by mass to 100% by mass, and particularly preferably 95% by mass to 100% by mass.

[0099] The polylactic acid resin composition containing the polylactic acid resin and the modifier may be prepared by previously mixing the polylactic acid resin, the modifier, and other components as necessary. Examples of the method for mixing include a mixing method using a mixer such as a tumbler, a ribbon blender, a V blender, a Henschel mixer, or a Redigay mixer.

[0100] As the extruder, any appropriate extruder may be used as long as the effects of the present invention are not impaired. In terms of being able to more effectively exhibit the effects of the present invention, the extruder is preferably a twin-screw extruder.

[0101] The twin-screw extruder may be equipped with a strand die or a T-die. In this case, the extruded strand- or sheet-shaped kneaded product may be cooled and cut with a pelletizer or the like to be pelletized.

[0102] The twin-screw extruder may be equipped with a pelletizing die (hot-cut die), in which case the kneaded material is pelletized immediately after extrusion.

[0103] The temperature conditions for melt kneading may vary depending on the size of the extruder, the discharge amount, etc., and any appropriate conditions may be adopted as long as the effects of the present invention are not impaired. For example, the temperature of the raw material feed section is preferably set to 100°C to 200°C.

[0104] The rotation speed of the extruder may vary depending on the size of the extruder, the discharge amount, etc., and any appropriate condition may be adopted as long as the effects of the present invention are not impaired. For example, such a rotation speed is preferably 20 rpm to 800 rpm.

[0105] The modified polylactic acid resin may be a dried one. Typically, the modified polylactic acid resin may be a pellet obtained by cooling a strand-shaped kneaded product extruded from a twin-screw extruder equipped with a strand die, cutting the kneaded product with a pelletizer, etc., and drying the pellets.

[0106] The modified polylactic acid resin can be produced using any appropriate device as long as the effects of the present invention are not impaired. For example, the modified polylactic acid resin can be produced using a production device as shown in FIG.

[0107] In FIG. 2, for example, polylactic acid resin and a modifier are charged into a hopper 11, melt-kneaded by a twin-screw extruder 30, and the strand-shaped kneaded material extruded from a strand die 3 is cooled by a cooling device 6, and then pelletized by a pelletizer 4 and dried by a drying device 5 to obtain a modified polylactic acid resin.

[0108] [Foaming Agent] Examples of components for foaming that can be used when producing a biodegradable polyester resin foam sheet from a resin composition include a foaming agent and a bubble adjuster. The resin composition typically contains a foaming agent. The foaming agent may be one type or two or more types.

[0109] As the foaming agent, any appropriate foaming agent can be used within a range that does not impair the effects of the present invention. Examples of the foaming agent include a volatile foaming agent that becomes gas at room temperature (23°C) and normal pressure (1 atm) and a decomposition type foaming agent that generates gas by thermal decomposition, and a volatile foaming agent is preferred.

[0110] The volatile foaming agent is preferably an organic compound whose boiling point is equal to or lower than the softening point of polylactic acid resin and is in a gaseous or liquid state at normal pressure.Specific examples include aliphatic hydrocarbons such as propane, n-butane, isobutane, pentane (n-pentane, isopentane, neopentane), and n-hexane; alicyclic hydrocarbons such as cyclopentane and cyclopentadiene; ketones such as acetone and methyl ethyl ketone; alcohols such as methanol, ethanol, and isopropyl alcohol; low-boiling ether compounds such as dimethyl ether, diethyl ether, dipropyl ether, and methyl ethyl ether; halogen-containing hydrocarbons such as trichloromonofluoromethane and dichlorodifluoromethane.The volatile foaming agent may also be an inorganic gas such as carbon dioxide, nitrogen, or ammonia. Among these, in terms of further exerting the effects of the present invention, the volatile blowing agent is preferably at least one selected from n-butane, isobutane, n-pentane, isopentane, neopentane, cyclopentane, and cyclopentadiene, and more preferably at least one selected from n-butane, isobutane, n-pentane, and isopentane.

[0111] Decomposition type foaming agents include, for example, azodicarbonamide, dinitrosopentamethylenetetramine, sodium bicarbonate, or a mixture of an organic acid or its salt, such as citric acid, and a bicarbonate.

[0112] The amount of the foaming agent used can be appropriately set depending on the purpose. The amount of the foaming agent used is preferably 0.1 to 10.0 parts by mass, more preferably 0.3 to 7.0 parts by mass, still more preferably 0.5 to 5.0 parts by mass, and particularly preferably 0.8 to 3.0 parts by mass, relative to 100 parts by mass of the biodegradable polyester resin.

[0113] [Air bubble adjuster] The resin composition may contain a cell regulator. The cell regulator may be of one type or of two or more types.

[0114] Examples of the foam regulator include higher fatty acid amides, partial esters of higher fatty acids and alcohols, talc, calcium carbonate, mica, citric acid, sodium bicarbonate, polytetrafluoroethylene, aluminum hydroxide, and silica. Examples of the higher fatty acid amides include fatty acid monoamides such as oleic acid amide, stearic acid amide, and hydroxystearic acid amide; and fatty acid bisamides such as methylene bisstearic acid amide and ethylene bisstearic acid amide. Examples of the higher fatty acids in the partial esters of higher fatty acids and alcohols include fatty acids having 15 or more carbon atoms, such as palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, and behenic acid. Examples of the partial esters of higher fatty acids and alcohols include stearic acid monoglyceride and stearic acid diglyceride.

[0115] The content of the cell regulator in the resin composition is preferably 0.01 mass% to 20 mass%, more preferably 0.1 mass% to 10 mass%, even more preferably 0.2 mass% to 5.0 mass%, and particularly preferably 0.3 mass% to 4.0 mass%, in order to further exert the effects of the present invention.

[0116] [Other ingredients] The resin composition may contain any appropriate other components as long as the effects of the present invention are not impaired. Such other components may be only one type or two or more types. Examples of such other components include foaming assistants, other resins, pigments, radiant heat transfer suppressing components, crosslinking agents, plasticizers, stabilizers, fillers, lubricants, colorants, antioxidants, antistatic agents, spreading agents, weather resistance agents, flame retardants, ultraviolet absorbers, light stabilizers, antiaging agents, antifogging agents, fragrances, and antibacterial agents.

[0117] The content ratio of other components in the resin composition may be any appropriate content ratio within the range that does not impair the effects of the present invention. Such a content ratio is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, particularly preferably 3% by mass or less, and most preferably 1% by mass or less.

[0118] <1-3-b. Production of biodegradable polyester resin foam> The biodegradable polyester resin foam is typically a biodegradable polyester resin foam sheet obtained by melt-kneading and extrusion-foaming a resin composition containing a biodegradable polyester resin in an extruder, or a biodegradable polyester resin foam molded product obtained by molding the foam sheet. That is, the biodegradable polyester resin foam is obtained by melt-kneading and extrusion-foaming a resin composition containing a biodegradable polyester resin in an extruder.

[0119] The biodegradable polyester resin foam molded article can be obtained by molding a biodegradable polyester resin foam sheet. Typically, the biodegradable polyester resin foam molded article can be obtained by heating and softening the biodegradable polyester resin foam sheet, and subjecting it to thermoforming using a mold, such as a vacuum molding method and / or a pressure molding method, or a matched mold molding method or a plug-assist molding method that is an application of the above.

[0120] Any components contained in the resin composition may be mixed in advance, if necessary, before being fed to the extruder. Examples of such a mixing method include a mixing method using a mixer such as a tumbler, a ribbon blender, a V blender, a Henschel mixer, or a Redigay mixer.

[0121] As the extruder, any appropriate extruder may be used as long as the effects of the present invention are not impaired. In terms of being able to more effectively exhibit the effects of the present invention, a tandem extruder is preferably used as the extruder.

[0122] The tip of the tandem extruder is provided with any appropriate die so as to finally obtain a biodegradable polyester resin foam sheet, as long as the effects of the present invention are not impaired. Preferably, the extruder may further be provided with a cooling mandrel, a take-up roller for taking up the biodegradable polyester resin foam sheet as a raw roll, and the like.

[0123] The biodegradable polyester resin foam sheet can be produced by using any appropriate apparatus, for example, a production apparatus as shown in FIG.

[0124] The production apparatus shown in Fig. 3 includes a tandem extruder 10 and a circular die CD for discharging the polylactic acid resin composition melt-kneaded in the tandem extruder 10 into a cylindrical shape. The production apparatus further includes a cooling device CL for air-cooling the foamed sheet discharged from the circular die CD into a cylindrical shape, a mandrel MD for expanding the diameter of the cylindrical foamed sheet into a cylindrical shape of a predetermined size, a slitting device for slitting the foamed sheet after passing through the mandrel MD and dividing it into two sheets, and a take-up roller 22 for winding up the slit foamed sheet 1 after passing through a plurality of rollers 21. The extruder upstream of the tandem extruder 10 (hereinafter also referred to as "first extruder 10a") includes a hopper 11 for introducing a biodegradable polyester resin, which is a raw material for the foamed sheet, and a gas introduction section 12 for supplying a foaming agent into the cylinder. An extruder (hereinafter also referred to as "second extruder 10b") for melt-kneading a resin composition containing a biodegradable polyester resin and a foaming agent is provided downstream of the first extruder 10a.

[0125] The temperature conditions of the melt kneading may vary depending on the size and discharge amount of the extruder, and therefore any appropriate conditions may be adopted within a range that does not impair the effects of the present invention. For example, the temperature of the raw material feed section of the upstream extruder 10a is preferably set to 100°C to 200°C, more preferably 140°C to 200°C, the temperature after the upstream extruder 10a is preferably set to 120°C to 300°C, more preferably 140°C to 270°C, and the temperature of the downstream extruder 10b is preferably set to 100°C to 250°C, more preferably 120°C to 220°C.

[0126] The rotation speed of the extruder may vary depending on the size of the extruder, the discharge amount, etc., and any appropriate condition may be adopted within a range that does not impair the effects of the present invention. For example, the rotation speed of the upstream extruder 10a is preferably 10 rpm to 300 rpm, and the rotation speed of the downstream extruder 10b is preferably 5 rpm to 200 rpm.

[0127] ≪≪2. Recycled biodegradable polyester resin foam sheet≫≫ The recycled biodegradable polyester resin foam sheet according to an embodiment of the present invention is obtained by foaming a recycled resin composition containing a recycled biodegradable polyester resin according to an embodiment of the present invention. The recycled biodegradable polyester resin foam sheet according to one embodiment of the present invention is obtained by melt-kneading a recycled resin composition containing a recycled biodegradable polyester resin in an extruder and extruding and foaming it. The recycled biodegradable polyester resin foam sheet according to an embodiment of the present invention has excellent foaming properties by using the recycled resin composition containing a recycled biodegradable polyester resin according to an embodiment of the present invention as a raw material.

[0128] In the recycled biodegradable polyester resin foam sheet according to the embodiment of the present invention, in a graph in which the horizontal axis is the logarithm of the strain amount ε (unit: dimensionless) obtained by uniaxial extensional viscosity measurement at 160°C and the vertical axis is the logarithm of the extensional viscosity η (Pa·s), the slope a3 of the graph in the direction from the inflection point toward an increase in the strain amount is typically 0.30 (Pa·s) or more, preferably 0.35 (Pa·s) or more, more preferably 0.40 (Pa·s) or more, and particularly preferably 0.45 (Pa·s) or more. The upper limit of the slope a1 of the graph is preferably 4.00 (Pa·s) or less, more preferably 3.00 (Pa·s) or less, even more preferably 2.50 (Pa·s) or less, particularly preferably 2.00 (Pa·s) or less, and most preferably 1.50 (Pa·s) or less, in order to further exhibit the effects of the present invention. When the slope a3 of the graph is within the above range, the recycled biodegradable polyester resin foam sheet according to the embodiment of the present invention can have excellent foaming properties.

[0129] The thickness of the recycled biodegradable polyester resin foam sheet according to the embodiment of the present invention can be appropriately set depending on the purpose. In one embodiment of the recycled biodegradable polyester resin foam sheet according to the embodiment of the present invention, the thickness is preferably 0.5 mm to 7 mm, more preferably 0.5 mm to 5 mm, further preferably 0.5 mm to 4 mm, and particularly preferably 0.5 mm to 3 mm.

[0130] The basis weight of the recycled biodegradable polyester resin foam sheet according to the embodiment of the present invention can be appropriately set depending on the purpose. In one embodiment of the recycled biodegradable polyester resin foam sheet according to the embodiment of the present invention, the basis weight is preferably 50 g / m 2 ~600g / m 2 and more preferably 100 g / m 2 ~550g / m 2 and more preferably 150 g / m 2 ~500g / m 2 and particularly preferably 200 g / m 2 ~450g / m 2It is.

[0131] The recycled biodegradable polyester resin foam sheet according to the embodiment of the present invention has an expansion ratio of preferably 4 to 20, more preferably 4 to 15, further preferably 4 to 12, and particularly preferably 4 to 10. The recycled biodegradable polyester resin foam sheet according to the embodiment of the present invention can achieve such a sufficient expansion ratio despite using recycled raw materials.

[0132] The recycled biodegradable polyester resin foam sheet according to the embodiment of the present invention has an open cell ratio of preferably 50% or less, more preferably 40% or less, even more preferably 30% or less, still more preferably 20% or less, particularly preferably 15% or less, and most preferably 12% or less. The recycled biodegradable polyester resin foam sheet according to the embodiment of the present invention can achieve such a low open cell ratio despite using recycled raw materials.

[0133] 2-1. Recycled resin composition One embodiment of the recycled biodegradable polyester resin foam sheet is obtained by melt-kneading a recycled resin composition containing a recycled biodegradable polyester resin according to an embodiment of the present invention in an extruder and extruding and foaming it.

[0134] The content ratio of the recycled biodegradable polyester resin according to an embodiment of the present invention in the recycled resin composition is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and even more preferably 90% by mass to 100% by mass, in order to achieve the effects of the present invention.

[0135] <2-1-a. Recycled biodegradable polyester resin> The recycled biodegradable polyester resin contained in the recycled resin composition is a recycled biodegradable polyester resin according to an embodiment of the present invention. For the recycled biodegradable polyester resin according to an embodiment of the present invention, the description in the above section "1. Recycled biodegradable polyester resin" may be used.

[0136] <2-1-b. Foaming agents> The recycled resin composition typically contains a foaming agent in addition to the recycled biodegradable polyester resin. The foaming agent may be one type or two or more types. For the foaming agent, the explanation in the section [Foaming Agent] in the section <1-3-a. Resin Composition> above may be used.

[0137] <2-1-c. Foam regulator> The recycled resin composition may contain a bubble regulator. The bubble regulator may be one type or two or more types. For the bubble regulator, the explanation in the section [Bubble Regulator] in the section <1-3-a. Resin Composition> above may be used.

[0138] <2-1-d. Other ingredients> The recycled resin composition may contain any appropriate other components within the scope of the present invention. Such other components may be one type only or two or more types. For such other components, the explanation in the section [Other Components] in the section <1-3-a. Resin Composition> above may be used.

[0139] ≪2-2. Manufacturing of recycled biodegradable polyester resin foam sheets≫ The recycled biodegradable polyester resin foam sheet according to one embodiment of the present invention is obtained by melt-kneading a recycled resin composition containing a recycled biodegradable polyester resin in an extruder and extruding and foaming the same.

[0140] Any components contained in the recycled resin composition may be mixed in advance, if necessary, before being fed to the extruder. Examples of such a mixing method include a mixing method using a mixer such as a tumbler, a ribbon blender, a V blender, a Henschel mixer, or a Redigay mixer.

[0141] As the extruder, any appropriate extruder may be used as long as the effects of the present invention are not impaired. In terms of being able to more effectively exhibit the effects of the present invention, a tandem extruder is preferably used as the extruder.

[0142] At the tip of the tandem extruder, any appropriate die may be provided so as to finally obtain a biodegradable polyester resin foam sheet, as long as the effects of the present invention are not impaired. Preferably, the extruder may further be provided with a cooling mandrel, a winding roller for winding up the recycled biodegradable polyester resin foam sheet into a raw roll, and the like.

[0143] The recycled biodegradable polyester resin foam sheet can be produced by using any appropriate device. For example, the recycled biodegradable polyester resin foam sheet can be produced by using the production device as shown in FIG. 3 described above as an example of the production device for the biodegradable polyester resin foam sheet.

[0144] The production apparatus shown in Fig. 3 includes a tandem extruder 10 and a circular die CD for discharging the polylactic acid resin composition melt-kneaded in the tandem extruder 10 into a cylindrical shape. The production apparatus further includes a cooling device CL for air-cooling the foamed sheet discharged from the circular die CD into a cylindrical shape, a mandrel MD for expanding the diameter of the cylindrical foamed sheet into a cylindrical shape of a predetermined size, a slitting device for slitting the foamed sheet after passing through the mandrel MD and dividing it into two sheets, and a take-up roller 22 for winding up the slit foamed sheet 1 after passing through a plurality of rollers 21. The extruder (hereinafter also referred to as "first extruder 10a") upstream of the tandem extruder 10 includes a hopper 11 for introducing a recycled biodegradable polyester resin, which is a raw material for the foamed sheet, and a gas introduction section 12 for supplying a foaming agent into the cylinder. An extruder (hereinafter also referred to as "second extruder 10b") for melt-kneading a resin composition containing recycled biodegradable polyester resin and a foaming agent is provided downstream of the first extruder 10a.

[0145] The temperature conditions of the melt kneading may vary depending on the size and discharge amount of the extruder, and therefore any appropriate conditions may be adopted within a range that does not impair the effects of the present invention. For example, the temperature of the raw material feed section of the upstream extruder 10a is preferably set to 100°C to 200°C, more preferably 140°C to 200°C, the temperature after the upstream extruder 10a is preferably set to 120°C to 300°C, more preferably 140°C to 270°C, and the temperature of the downstream extruder 10b is preferably set to 100°C to 250°C, more preferably 120°C to 220°C.

[0146] The rotation speed of the extruder may vary depending on the size of the extruder, the discharge amount, etc., and any appropriate condition may be adopted within a range that does not impair the effects of the present invention. For example, the rotation speed of the upstream extruder 10a is preferably 10 rpm to 300 rpm, and the rotation speed of the downstream extruder 10b is preferably 5 rpm to 200 rpm.

[0147] ≪≪3. Recycled biodegradable polyester resin foam molding≫≫ The recycled biodegradable polyester resin foam molded article according to the embodiment of the present invention is obtained by molding the recycled biodegradable polyester resin foam sheet according to the embodiment of the present invention. The recycled biodegradable polyester resin foam molded article according to the embodiment of the present invention can be obtained by, for example, heating and softening the recycled biodegradable polyester resin foam sheet according to the embodiment of the present invention, and subjecting the sheet to thermoforming such as vacuum molding and / or pressure molding, or a matched mold molding method or a plug assist molding method that is an application of the above, using a mold.

[0148] The recycled biodegradable polyester resin foam molded article according to the embodiment of the present invention may be, for example, food containers such as trays, cups, bowls, lunch boxes, fruit containers, vegetable containers, etc.; cushioning materials such as cushioning materials for electrical products and cushioning materials for precision instruments; and the like. EXAMPLES

[0149] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring and evaluating each property are as follows.

[0150] <Uniaxial extensional viscosity measurement> A graph was obtained by measuring the uniaxial extensional viscosity of a resin at 160°C, with the horizontal axis representing the logarithm of the strain amount ε (unit: dimensionless) and the vertical axis representing the logarithm of the extensional viscosity η (unit: Pa s) as shown below. The uniaxial extensional viscosity was measured using a viscoelasticity measuring device "PHYSICA MCR301" (manufactured by Anton Paar) and a temperature control system "CTD450" (manufactured by Anton Paar). First, the resin to be measured (if in the form of a foam, the foam) was pressed in a heat press at 190°C for 5 minutes to prepare a rectangular sample with a width of 10 mm and a thickness of about 0.8 mm. Next, this rectangular sample was cut into a length of 20 to 25 mm to prepare a test piece. The test piece was set in the uniaxial extensional viscosity measuring jig (SER2) of the viscoelasticity measuring device heated to 160°C, and after waiting for 10 seconds under a nitrogen atmosphere at a temperature condition of 160°C ± 0.5°C, the uniaxial extensional viscosity was measured at a strain rate of 1.0 / sec. The measurement point interval was set to "obtain measurement point interval logarithmically," with the start at 0.01 sec and the end at 26 sec. The measurement points were set to 200. The measurement results obtained were plotted on a double logarithmic axis graph, with the horizontal axis representing the common logarithmic value (log(ε)) of strain ε (unit: dimensionless) and the vertical axis representing the common logarithmic value (log(η)) of extensional viscosity η (unit: Pa s). A straight line was approximated from the inflection point to the strain at which the maximum extensional viscosity was obtained using the least squares method. As a representative example, FIG. 1 shows an example of a graph in which the horizontal axis represents the logarithm of the strain amount ε (unit: dimensionless) and the vertical axis represents the logarithm of the extensional viscosity η (unit: Pa·s) obtained by uniaxial extensional viscosity measurement at 160°C for a recycled biodegradable polyester resin according to one embodiment of the present invention. In FIG. 1, the horizontal axis represents the logarithm of the strain amount ε (unit: dimensionless), and the vertical axis represents the logarithm of the extensional viscosity η (unit: Pa·s). In FIG. 1, V is an inflection point. In the present invention, the slope a2 of the graph in the direction from the inflection point to the direction in which the strain amount increases is the slope of the straight line obtained by linear approximation by the least squares method for the curve from the inflection point V to the point where the extensional viscosity η is the maximum value in the direction in which the strain amount increases, when explained using FIG. 1 as an example. Note that in the recycled biodegradable polyester resin, the slope of the graph in the direction in which the strain amount decreases from the inflection point may be a negative value. The slopes a1 and a3 of the graph in the direction in which the strain increases from the inflection point were also measured in the same manner.

[0151] <Moisture content measurement> 1.0 g of the sample was set in a Karl Fischer moisture analyzer (manufactured by Mitsubishi Chemical Analytech Co., Ltd., "CA-200") and a moisture vaporizer (manufactured by Mitsubishi Chemical Analytech Co., Ltd., "VA-236S") to measure the actually measured moisture content. For the anode liquid and cathode liquid during the measurement, Aquamicron AX and Aquamicron CXU manufactured by Mitsubishi Chemical Corporation were used respectively. The measurement temperature was set at 128 °C. N2 was used as the carrier gas. The flow rate of the carrier gas was set at 250 mL / min. The measurement of the actually measured moisture content was performed 3 times. On the other hand, the moisture content was measured twice only under the air atmosphere at the sample collection location, and the average value was taken as the blank moisture content. Using each of the actually measured moisture contents obtained from the above three measurements, the moisture content (mass%) was calculated by the following formula, and the three calculated results obtained were averaged to obtain the moisture content (mass%) of the sample. Moisture content (mass%) = [〔Actually measured moisture content (μg) - Blank moisture content (μg)〕÷ 1000000 ÷ Sample mass (g)] × 100

[0152] <Measurement of MFR (Melt Mass Flow Rate)> The MFR was measured in accordance with the standard of JIS K 7210:1999. Specifically, it was measured by the method of "b) Measuring the time for the piston to move a predetermined distance" described in Method B of the standard of JIS K 7210:1999. The MFR was measured using a melt flow index tester (automatic) 120-SAS (manufactured by Yasuda Seiki Seisakusho Co., Ltd.). The sample used was one that had been vacuum-dried at 70 °C for 5 hours and stored in a desiccator sealed until immediately before the measurement. The number of measurements was 3 times, and the average value was adopted. The measurement conditions were as follows. Sample: 3 g to 8 g Preheating (1): 200 seconds Preheating (2): 30 seconds Test temperature: 190 °C Test load: 21.18 N Piston movement distance (interval): 25 mm

[0153] <Measurement of melt tension> The melt tension was measured using a Capilograph 1D (manufactured by Toyo Seiki Seisakusho Co., Ltd.) and a Rheotens 71.97 (manufactured by Gottfert). The sample was vacuum dried at 70°C for 5 hours in advance. Rheotens 71.97 was installed so that the distance from the capillary die outlet of the Capillograph 1D to the measurement section was 80 mm. First, the sample was filled into a 9.55 mm diameter barrel heated to a test temperature of 190°C, and then preheated for 5 minutes. The measurement time must not exceed 10 minutes, including the preheating time, after filling the barrel. Next, a piston was inserted from the top of the barrel, and the molten resin was extruded in a string-like shape from the capillary die (diameter 2.095 mm, length 8 mm, inlet angle 90 degrees (conical)). At this time, the piston descent speed (20 mm / min) was kept constant, and the extruded string-like material was passed through the Rheotens wheel (wheel interval: upper 0.6 mm to 0.8 mm, lower 1.0 mm), and the take-up speed was set to an initial speed of 6.92 mm / s and an acceleration of 10 mm / s. 2 The melt tension of the sample was measured while gradually increasing the temperature. Regarding the measurement results, the average of the maximum and minimum tension values ​​just before the point at which the string broke was taken as the melt tension of the sample. When there was only one maximum point on the tension chart, the maximum value was regarded as the melt tension. When the string-like material became thinner and the winding started to rotate freely, that point was regarded as the breaking point, and the average of the maximum and minimum tension values ​​immediately before that point was regarded as the melt tension of the sample. [Measurement conditions for "Capillograph 1D"] Die: diameter 2.095mm, length 8mm, inlet angle 90 degrees (conical) Barrel diameter: 9.55mm Piston speed: 20mm / min Measurement temperature: 190℃ [Measurement conditions for "Rheotens 71.97"] Wheel spacing: Top 0.6mm~0.8mm, bottom 1.0mm Acceleration: 10mm / s 2 Pulling speed: Initial speed 6.92mm / s

[0154] <Molecular weight measurement> The number average molecular weight (Mn), weight average molecular weight (Mw), and Z average molecular weight (Mz) were each determined as follows. 20 mg of the sample to be measured for molecular weight was dissolved in 6 mL of chloroform (immersion time: 6 hours ± 1.0 hour (partially insoluble)), filtered through a non-aqueous 0.45 μm syringe filter manufactured by Shimadzu GLC Co., Ltd., and then measured using a chromatograph under the following measurement conditions, and the average molecular weight of the sample was calculated from a standard polystyrene calibration curve prepared in advance. The equipment used was a gel permeation chromatograph manufactured by Tosoh Corporation ("HLC-8320GPC EcoSEC", with built-in RI and UV detectors). [GPC measurement conditions] Guard column: TSK guardcolumn HXL-H (6.0 mm x 4.0 cm) x 1, manufactured by Tosoh Corporation Measurement column: Tosoh Corporation's TSKgel GMHXL (7.8 mm I.D. x 30 cm) x 2 in series Reference side: Resistance tube (inner diameter 0.1 mm x 2 m) x 2 in series Column temperature: 40℃ Mobile phase: Chloroform Reference pump mobile phase flow rate: 0.5mL / min Mobile phase flow rate of sample pump: 1.0mL / min Detector: RI detector Injection volume: 50μL Measurement time: Measurement time: 25 min Sampling pitch: 500msec The standard polystyrene samples used for the calibration curve were "STANDARD SM-105" and "STANDARD SH-75" manufactured by Showa Denko K.K., with mass average molecular weights of 5,620,000, 3,120,000, 1,250,000, 442,000, 151,000, 53,500, 17,000, 7,660, 2,900, and 1,320. The above-mentioned standard polystyrene for the calibration curve was grouped into A (5,620,000, 1,250,000, 151,000, 17,000, 2,900) and B (3,120,000, 442,000, 53,500, 7,660, 1,320), and then A was weighed out to (2 mg, 3 mg, 4 mg, 4 mg, 4 mg) and dissolved in 30 mL of chloroform, and B was weighed out to (3 mg, 4 mg, 4 mg, 4 mg, 4 mg) and dissolved in 30 mL of chloroform. The standard polystyrene calibration curve was obtained by creating a calibration curve (cubic equation) from the retention time obtained after injecting 50 μL of each prepared solution A and each solution B. The average molecular weight was calculated using the calibration curve.

[0155] <Measurement of melting point and crystallization temperature> The melting point and crystallization temperature were measured using a heat flux differential scanning calorimeter (heat flux DSC) according to the methods described in JIS K7122:1987, JIS K7122:2012 "Method of measuring heat of transition of plastics" and JIS K7121:1987, 2012 "Method of measuring transition temperature of plastics". The sampling method and temperature conditions were as follows: The sample was packed so that there were no gaps at the bottom of an aluminum measurement container (Hitachi High-Tech Science Corporation, product code: GAA-0065) at 5.5±0.5 mg, and then an aluminum lid (Hitachi High-Tech Science Corporation, product code: GAA-0064) was placed on the container. Then, using a differential scanning calorimeter (Hitachi High-Tech Science Corporation, "NEXTA DSC600"), the sample was heated and cooled in the following steps under a nitrogen gas flow rate of 20 mL / min to obtain a DSC curve. (Step 1) Heat from 30°C to 210°C (first heating) and then hold for 10 minutes. (Step 2) Remove from the measurement device, leave at room temperature for 10 minutes, and then return to the measurement device at 30°C (rapid cooling). (Step 3) Increase the temperature from 30°C to 210°C (second increase in temperature). All the heating was performed at a rate of 5° C. / min. Alumina was used as the reference material. (Melting Point) Using the analysis software attached to the apparatus, the top temperature of the melting peak observed during the second heating process was read and regarded as the melting temperature (melting point). (crystallization temperature) The crystallization temperature was determined by reading the top temperature of the exothermic peak observed during the second heating process. When multiple exothermic peaks appeared, the temperature of the lowest peak was read.

[0156] <Measurement of foam sheet thickness> The thickness of the foamed sheet in the width direction (TD direction) except for 20 mm at both ends was measured at nine equally spaced points in the width direction using a dial thickness gauge SM-112 (manufactured by Techlock), and the arithmetic mean of the measured values ​​was regarded as the thickness of the foamed sheet.

[0157] <Measurement of basis weight of foam sheet> Six pieces of 10 cm x 10 cm were cut out at equal intervals in the width direction of the foam sheet, excluding 20 mm at both ends in the width direction (TD direction), and the mass (g) of each piece was measured to the nearest 0.001 g. The average mass (g) of each piece was calculated as 1 m. 2 The converted value is the basis weight (g / m2) of the foam sheet. 2 ) was decided.

[0158] <Measurement of apparent density> The apparent density was measured by the method described in JIS K7222:1999 "Foamed plastics and rubber - Measurement of apparent density". Specifically, the apparent density was measured by the following method. From foam sheet or foam molding, 100 cm 3 The above samples were cut without changing the original cell structure, and the samples were conditioned for 16 hours in a JIS K7100:1999, symbol 23 / 50, class 2 environment, after which the dimensions and mass were measured, and the density was calculated according to the following formula. Apparent density (kg / m 3 ) = mass of sample (kg) / volume of sample (m 3 ) The dimensions of the samples were measured using a "DIGIMATIC" CD-15 type manufactured by Mitutoyo Corporation.

[0159] <Measurement of foaming ratio> The expansion ratio of the biodegradable polyester resin foam sheet was determined by determining the apparent density (ρ1) of the biodegradable polyester resin foam sheet, determining the density (true density: ρ0) of the resin composition constituting the biodegradable polyester resin foam sheet, and dividing the true density (ρ0) by the apparent density (ρ1). Expansion ratio = true density (ρ0) / apparent density (ρ1) The density of the biodegradable polyester resin foam sheet can be determined by the method described in JIS-K7222:1999 "Foamed plastics and rubber - Measurement of apparent density", and specifically, it was determined by the following method. (Density measurement method) From biodegradable polyester resin foam sheet, 100cm 3 The above samples were cut without changing the original cell structure, and the samples were conditioned for 16 hours in a JIS K7100:1999, symbol 23 / 50, class 2 environment, after which the dimensions and mass were measured, and the density was calculated according to the following formula. Apparent density (kg / m 3 ) = mass of sample (kg) / volume of sample (m 3 ) The dimensions of the samples were measured using a "DIGIMATIC" CD-15 type manufactured by Mitutoyo Corporation. The density of the resin composition constituting the biodegradable polyester resin foam sheet was determined by measuring a sample prepared by heat pressing the biodegradable polyester resin foam sheet to make it non-foamed, based on the Archimedes method (the liquid weighing method according to JIS-K8807:2012 "Methods for determining density and specific gravity of solids").

[0160] <Measurement of open cell ratio> Cut out several sheet-like samples measuring 25 mm in length and 25 mm in width from the foam sheet, stack the cut samples together without leaving any gaps to make a measurement sample with a thickness of 25 mm, measure the outer dimensions of this measurement sample to 1 / 100 mm using a Mitutoyo Corporation "Digimatic Caliper", and calculate the apparent volume (cm 3 ) was sought. Next, the volume (cm) of the sample to be measured was measured using an air comparison type specific gravity meter Model 1000 (Tokyo Science Co., Ltd.) by the 1-1 / 2-1 atmospheric pressure method. 3 ) was sought. The open cell ratio (%) was calculated from these determined values ​​and the following formula, and the average value for five test pieces was calculated. The measurement was performed in a JIS K7100-1999, symbol 23 / 50, grade 2 environment after conditioning the measurement sample for 16 hours in the JIS K7100-1999, symbol 23 / 50, grade 2 environment. In addition, the air comparison type specific gravity meter was calibrated using standard bulbs (large 28.9cc, small 8.5cc). Open cell rate (%) = [(apparent volume - volume measured with air comparison type specific gravity meter) / apparent volume] x 100 (%)

[0161] [Production Example 1] Polylactic acid resin (Nature Works LLC, "Biopolymer Ingeo 6202D", MFR = 11.2 g / 10 min, density = 1240 kg / m 3 The moisture content of the polylactic acid resin was adjusted to 0.02% by mass. 100 parts by mass of this polylactic acid resin with a moisture content of 0.02% by mass and 0.5 parts by mass of t-butylperoxyisopropyl monocarbonate (manufactured by Kayaku Nouryon Co., Ltd., "Trigonox BPIC-75", 1-minute half-life temperature T1 = 158.8°C) were stirred and mixed in a ribbon blender to obtain a mixture. The resulting mixture was fed into a twin-screw extruder with a diameter of 57 mm (L / D=31.5). The temperature setting for the feed section was set to 170°C, and the temperature thereafter to 200°C. The mixture was melt-kneaded in the twin-screw extruder at a rotation speed of 100 rpm, and the kneaded material was extruded in the form of strands at a discharge rate of 50 kg / hour from a die (diameter φ3 mm, number of holes 18) attached to the tip of the extruder. Next, the extruded strand-like kneaded product was passed through a 2 m long cooling water tank containing water at 30° C. to cool it. The cooled strands were cut by a pelletizer to form pellets, and then dried in a dehumidifying dryer at a drying temperature of 70° C. The moisture content of the resulting pellets of modified polylactic acid resin (1) was 0.02% by mass. The physical properties of the resulting modified polylactic acid resin (1) are shown in Tables 1 and 2.

[0162] [Production Example 2] Polylactic acid resin (product name "FY602", manufactured by Anhui Fengyuan Futarai Lactic Acid Co., Ltd., MFR = 16.0g / 10min, D-form ratio = 2.0±0.5mol%, melting point = 164.3℃, density = 1240kg / m 3 The moisture content of the polylactic acid resin was adjusted to 0.04% by mass. 100 parts by mass of this polylactic acid resin with a moisture content of 0.04% by mass and 0.5 parts by mass of t-butylperoxyisopropyl monocarbonate (manufactured by Kayaku Nouryon Co., Ltd., "Trigonox BPIC-75", 1-minute half-life temperature T1 = 158.8°C) were stirred and mixed in a ribbon blender to obtain a mixture. The resulting mixture was fed into a twin-screw extruder with a diameter of 57 mm (L / D=31.5). The temperature setting for the feed section was set to 170°C, and the temperature thereafter to 200°C. The mixture was melt-kneaded in the twin-screw extruder at a rotation speed of 100 rpm, and the kneaded material was extruded in the form of strands at a discharge rate of 50 kg / hour from a die (diameter φ3 mm, number of holes 18) attached to the tip of the extruder. Next, the extruded strand-like kneaded product was passed through a 2 m long cooling water tank containing water at 30° C. to cool it. The cooled strands were cut by a pelletizer to form pellets, and then dried in a dehumidifying dryer at a drying temperature of 70° C. The moisture content of the resulting pellets of modified polylactic acid resin (2) was 0.03% by mass. The physical properties of the resulting modified polylactic acid resin (2) are shown in Tables 1 and 2.

[0163] [Table 1]

[0164] [Table 2]

[0165] [Production Example 3] A mixture was prepared by dry blending 100 parts by mass of the modified polylactic acid resin (1) (moisture content: 0.02% by mass) obtained in Production Example 1 and 1.0 part by mass of a cell regulator ("Crown Talc" manufactured by Matsumura Sangyo Co., Ltd.). In a tandem extruder equipped with a first extruder (upstream) with a diameter of φ50 mm and a second extruder (downstream) with a diameter of φ65 mm, the above mixture was supplied to the first extruder with a diameter of φ50 mm through a hopper and heated and melted at 220°C. In addition, in order to confirm whether the moisture content of the modified polylactic acid resin (1) changes between the time when the modified polylactic acid resin (1) is prepared and the time when it is supplied to the hopper, the moisture content of the modified polylactic acid resin (1) sampled in the hopper when only the modified polylactic acid resin (1) is supplied to the first extruder through the hopper was checked, and it remained at 0.02 mass%. Thereafter, 1.2 parts by mass of butane (isobutane / normal butane=35% by mass / 65% by mass) as a foaming agent was pressure-fed into the first extruder and melt-kneaded together with the above mixture. The molten mixture was then transferred to a second extruder having an aperture of φ65 mm and cooled to 170° C., after which it was extruded and foamed through a circular die having an aperture of φ70 mm at a discharge rate of 30 kg / hour to obtain a cylindrical foam. The obtained cylindrical foam was placed on a φ206 mm mandrel whose inside was cooled with water at about 20°C, and its outer surface was cooled and molded by blowing air onto it using an air ring larger than its diameter. Then, it was cut at one point on the circumference using a cutter to obtain a belt-shaped polylactic acid resin foam sheet (1). The physical properties of the resulting polylactic acid resin foam sheet (1) are shown in Table 3.

[0166] [Production Example 4] The modified polylactic acid resin (2) obtained in Production Example 2 (moisture content: 0.03% by mass): 100 parts by mass and a cell regulator ("Crown Talc" manufactured by Matsumura Sangyo Co., Ltd.): 1.0 part by mass were dry blended to prepare a mixture. In a tandem extruder equipped with a first extruder (upstream) with a diameter of φ50 mm and a second extruder (downstream) with a diameter of φ65 mm, the above mixture was supplied to the first extruder with a diameter of φ50 mm through a hopper and heated and melted at 220°C. In addition, in order to confirm whether the moisture content of the modified polylactic acid resin (2) changes between the time when the modified polylactic acid resin (2) is prepared and the time when it is supplied to the hopper, the moisture content of the modified polylactic acid resin (2) sampled in the hopper when only the modified polylactic acid resin (2) is supplied to the first extruder through the hopper was checked, and it remained at 0.02 mass%. Thereafter, 1.2 parts by mass of butane (isobutane / normal butane=35% by mass / 65% by mass) as a foaming agent was pressure-fed into the first extruder and melt-kneaded together with the above mixture. The molten mixture was then transferred to a second extruder having an aperture of φ65 mm and cooled to 170° C., after which it was extruded and foamed through a circular die having an aperture of φ70 mm at a discharge rate of 30 kg / hour to obtain a cylindrical foam. The obtained cylindrical foam was placed on a φ206 mm mandrel whose inside was cooled with water at about 20°C, and its outer surface was cooled and molded by blowing air onto it using an air ring larger than its diameter. It was then cut at one point on the circumference with a cutter to obtain a belt-shaped polylactic acid resin foam sheet (2). The physical properties of the resulting polylactic acid resin foam sheet (2) are shown in Table 3.

[0167] [Production Example 5] A modified polylactic acid resin was produced in the same manner as in Production Example 2, but due to insufficient drying, the moisture content of the resulting modified polylactic acid resin (3) was 0.16 mass%. Using this modified polylactic acid resin (3), a polylactic acid resin foam sheet (3) was obtained in the same manner as in Production Example 4. The physical properties of the resulting polylactic acid resin foam sheet (3) are shown in Table 3.

[0168] [Production Example 6] A modified polylactic acid resin was produced in the same manner as in Production Example 2, but due to insufficient drying, the moisture content of the resulting modified polylactic acid resin (4) was 0.28 mass%. A polylactic acid resin foam sheet (4) was obtained using the same method as in Production Example 4. The physical properties of the resulting polylactic acid resin foam sheet (4) are shown in Table 3.

[0169] [Production Example 7] A modified polylactic acid resin was produced in the same manner as in Production Example 2. However, due to insufficient drying, the moisture content of the resulting modified polylactic acid resin (5) was 0.37% by mass. An attempt was made to obtain a polylactic acid resin foam sheet using the same method as in Production Example 4, but molten resin was discharged from the circular die, and a foam sheet could not be obtained. The results are shown in Table 3.

[0170] [Table 3]

[0171] [Example 1] The polylactic acid resin foam sheet (1) obtained in Production Example 3 was used as a recycled raw material, which was pulverized to obtain a pulverized material, which was then fed into a twin-screw extruder having an aperture of 57 mm (L / D=31.5). The set temperature of the feed section was set to 170°C, and the temperature thereafter to 200°C, and the rotation speed was set to 100 rpm. The pulverized material was melt-kneaded in the twin-screw extruder, and the kneaded material was extruded in the form of strands at a discharge rate of 50 kg / hour from a die (diameter φ3 mm, number of holes) attached to the tip of the extruder. Next, the extruded strand-like kneaded product was passed through a 2 m long cooling water tank containing water at 30° C. to cool it. The cooled strands were cut by a pelletizer to form pellets, and then dried in a dehumidifying dryer at a drying temperature of 70° C. The moisture content of the resulting recycled polylactic acid resin (1) was 0.04% by mass. The physical properties of the resulting recycled polylactic acid resin (1) are shown in Table 4.

[0172] [Example 2] The polylactic acid resin foam sheet (2) obtained in Production Example 4 was used as a recycled raw material, which was pulverized to obtain a pulverized material, which was then fed into a twin-screw extruder having an aperture of 57 mm (L / D=31.5). The set temperature of the feed section was set to 170°C, and the temperature thereafter to 200°C, and the rotation speed was set to 100 rpm. The pulverized material was melt-kneaded in the twin-screw extruder, and the kneaded material was extruded in the form of strands at a discharge rate of 50 kg / hour from a die (diameter φ3 mm, number of holes) attached to the tip of the extruder. Next, the extruded strand-like kneaded product was passed through a 2 m long cooling water tank containing water at 30° C. to cool it. The cooled strands were cut by a pelletizer to form pellets, and then dried in a dehumidifying dryer at a drying temperature of 70° C. The moisture content of the resulting recycled polylactic acid resin (2) was 0.03% by mass. The physical properties of the resulting recycled polylactic acid resin (2) are shown in Table 4.

[0173] [Example 3] The polylactic acid resin foam sheet (3) obtained in Production Example 5 was used as a recycled raw material, which was pulverized to obtain a pulverized material, which was then fed into a twin-screw extruder having an aperture of 57 mm (L / D=31.5). The set temperature of the feed section was set to 170°C, and the temperature thereafter to 200°C, and the rotation speed was set to 100 rpm. The pulverized material was melt-kneaded in the twin-screw extruder, and the kneaded material was extruded in the form of strands at a discharge rate of 50 kg / hour from a die (diameter φ3 mm, number of holes) attached to the tip of the extruder. Next, the extruded strand-like kneaded product was passed through a 2 m long cooling water tank containing water at 30° C. to cool it. The cooled strands were cut by a pelletizer to form pellets, and then dried in a dehumidifying dryer at a drying temperature of 70° C. The moisture content of the resulting recycled polylactic acid resin (3) was 0.04% by mass. The physical properties of the resulting recycled polylactic acid resin (3) are shown in Table 4.

[0174] [Comparative Example 1] The polylactic acid resin foam sheet (4) obtained in Production Example 6 was used as a recycled raw material, which was pulverized to obtain a pulverized material, which was then fed into a twin-screw extruder having an aperture of 57 mm (L / D=31.5). The set temperature of the feed section was set to 170°C, and the temperature thereafter to 200°C, and the rotation speed was set to 100 rpm. The pulverized material was melt-kneaded in the twin-screw extruder, and the kneaded material was extruded in the form of strands at a discharge rate of 50 kg / hour from a die (diameter φ3 mm, number of holes) attached to the tip of the extruder. Next, the extruded strand-like kneaded product was passed through a 2 m long cooling water tank containing water at 30° C. to cool it. The cooled strands were cut by a pelletizer to form pellets, and then dried in a dehumidifying dryer at a drying temperature of 70° C. The moisture content of the resulting recycled polylactic acid resin (4) was 0.03% by mass. The physical properties of the resulting recycled polylactic acid resin (4) are shown in Table 4. The melt tension was below the lower limit of the measurable range (1 cN) and could not be measured.

[0175] [Table 4]

[0176] [Example 4] A mixture was prepared by dry blending 100 parts by mass of the recycled polylactic acid resin (1) obtained in Example 1 (moisture content: 0.04% by mass) and 1.0 part by mass of a cell regulator ("Crown Talc" manufactured by Matsumura Sangyo Co., Ltd.). In a tandem extruder equipped with a first extruder (upstream) with a diameter of φ50 mm and a second extruder (downstream) with a diameter of φ65 mm, the above mixture was supplied to the first extruder with a diameter of φ50 mm through a hopper and heated and melted at 220°C. In addition, in order to confirm whether the moisture content of the recycled polylactic acid resin (1) changes between the time when the recycled polylactic acid resin (1) is prepared and the time when it is supplied to the hopper, the moisture content of the recycled polylactic acid resin (1) sampled in the hopper when only the recycled polylactic acid resin (1) is supplied to the first extruder through the hopper was confirmed to be 0.04 mass%. Thereafter, 1.2 parts by mass of butane (isobutane / normal butane=35% by mass / 65% by mass) as a foaming agent was pressure-fed into the first extruder and melt-kneaded together with the above mixture. The molten mixture was then transferred to a second extruder having an aperture of φ65 mm and cooled to 170° C., after which it was extruded and foamed through a circular die having an aperture of φ70 mm at a discharge rate of 30 kg / hour to obtain a cylindrical foam. The obtained cylindrical foam was placed on a φ206 mm mandrel whose inside was cooled with water at about 20°C, and its outer surface was cooled and molded by blowing air onto it using an air ring larger than its diameter. It was then cut at one point on the circumference using a cutter to obtain a strip-shaped recycled polylactic acid resin foam sheet (1). The physical properties of the obtained recycled polylactic acid resin foam sheet (1) are shown in Table 5.

[0177] [Example 5] A mixture was prepared by dry blending 100 parts by mass of the recycled polylactic acid resin (2) (moisture content: 0.03% by mass) obtained in Example 2 and 1.0 part by mass of a cell regulator ("Crown Talc" manufactured by Matsumura Sangyo Co., Ltd.). In a tandem extruder equipped with a first extruder (upstream) with a diameter of φ50 mm and a second extruder (downstream) with a diameter of φ65 mm, the above mixture was supplied to the first extruder with a diameter of φ50 mm through a hopper and heated and melted at 220°C. In order to confirm whether the moisture content of the recycled polylactic acid resin (2) changes between the time when the recycled polylactic acid resin (2) is prepared and the time when the recycled polylactic acid resin (2) is supplied to the hopper, the moisture content of the recycled polylactic acid resin (2) sampled in the hopper when only the recycled polylactic acid resin (2) is supplied to the first extruder through the hopper was confirmed to be 0.03% by mass. Thereafter, 1.2 parts by mass of butane (isobutane / normal butane=35% by mass / 65% by mass) as a foaming agent was pressure-fed into the first extruder and melt-kneaded together with the above mixture. The molten mixture was then transferred to a second extruder having an aperture of φ65 mm and cooled to 170° C., after which it was extruded and foamed through a circular die having an aperture of φ70 mm at a discharge rate of 30 kg / hour to obtain a cylindrical foam. The obtained cylindrical foam was placed on a φ206 mm mandrel whose inside was cooled with water at about 20°C, and its outer surface was cooled and molded by blowing air onto it using an air ring larger than its diameter. It was then cut at one point on the circumference using a cutter to obtain a strip-shaped recycled polylactic acid resin foam sheet (2). The physical properties of the obtained recycled polylactic acid resin foam sheet (2) are shown in Table 5.

[0178] [Example 6] A mixture was prepared by dry blending 100 parts by mass of the recycled polylactic acid resin (3) (moisture content: 0.04% by mass) obtained in Example 3 and 1.0 part by mass of a cell regulator ("Crown Talc" manufactured by Matsumura Sangyo Co., Ltd.). In a tandem extruder equipped with a first extruder (upstream) with a diameter of φ50 mm and a second extruder (downstream) with a diameter of φ65 mm, the above mixture was supplied to the first extruder with a diameter of φ50 mm through a hopper and heated and melted at 220°C. In order to confirm whether the moisture content of the recycled polylactic acid resin (3) changes between the time when the recycled polylactic acid resin (3) is prepared and the time when the recycled polylactic acid resin (3) is supplied to the hopper, the moisture content of the recycled polylactic acid resin (3) sampled in the hopper when only the recycled polylactic acid resin (3) is supplied to the first extruder through the hopper was confirmed to be 0.04% by mass. Thereafter, 1.2 parts by mass of butane (isobutane / normal butane=35% by mass / 65% by mass) as a foaming agent was pressure-fed into the first extruder and melt-kneaded together with the above mixture. The molten mixture was then transferred to a second extruder having an aperture of φ65 mm and cooled to 170° C., after which it was extruded and foamed through a circular die having an aperture of φ70 mm at a discharge rate of 30 kg / hour to obtain a cylindrical foam. The obtained cylindrical foam was placed on a φ206 mm mandrel whose inside was cooled with water at about 20°C, and its outer surface was cooled and molded by blowing air onto it using an air ring larger than its diameter. It was then cut at one point on the circumference using a cutter to obtain a strip-shaped recycled polylactic acid resin foam sheet (3). The physical properties of the obtained recycled polylactic acid resin foam sheet (3) are shown in Table 5.

[0179] [Comparative Example 2] The recycled polylactic acid resin (4) obtained in Comparative Example 1 (moisture content: 0.03% by mass): 100 parts by mass and a cell regulator ("Crown Talc" manufactured by Matsumura Sangyo Co., Ltd.): 1.0 part by mass were dry blended to prepare a mixture. In a tandem extruder equipped with a first extruder (upstream) with a diameter of φ50 mm and a second extruder (downstream) with a diameter of φ65 mm, the above mixture was supplied to the first extruder with a diameter of φ50 mm through a hopper and heated and melted at 220°C. In order to confirm whether the moisture content of the recycled polylactic acid resin (4) changes between the time when the recycled polylactic acid resin (4) is prepared and the time when the recycled polylactic acid resin (4) is supplied to the hopper, the moisture content of the recycled polylactic acid resin (4) sampled in the hopper when only the recycled polylactic acid resin (4) is supplied to the first extruder through the hopper was confirmed to be 0.03% by mass. Thereafter, 1.2 parts by mass of butane (isobutane / normal butane=35% by mass / 65% by mass) as a foaming agent was pressure-fed into the first extruder and melt-kneaded together with the above mixture. Next, the molten mixture was transferred to a second extruder with an aperture of φ65 mm and cooled to 170°C, and then extrusion foaming was attempted at a discharge rate of 30 kg / hour from a circular die with an aperture of φ70 mm. However, the molten resin was discharged from the circular die, and a foamed sheet could not be obtained. The results are shown in Table 5.

[0180] [Table 5]

[0181] As shown in Table 5, the recycled polylactic acid resin foam sheet (1) obtained using the recycled polylactic acid resin (1) obtained in Example 1, the recycled polylactic acid resin foam sheet (2) obtained using the recycled polylactic acid resin (2) obtained in Example 2, and the recycled polylactic acid resin foam sheet (3) obtained using the recycled polylactic acid resin (3) obtained in Example 3 were able to exhibit sufficient expansion ratios despite the use of recycled raw materials, and were able to exhibit low open cell ratios despite the use of recycled raw materials. Therefore, the recycled polylactic acid resin foam sheet (1) obtained using the recycled polylactic acid resin (1) obtained in Example 1, the recycled polylactic acid resin foam sheet (2) obtained using the recycled polylactic acid resin (2) obtained in Example 2, and the recycled polylactic acid resin foam sheet (3) obtained using the recycled polylactic acid resin (3) obtained in Example 3 were able to suppress the decrease in foaming performance when made into a foamed sheet despite the use of recycled raw materials, and it can be said that they are beneficial for a recycling system for producing recycled biodegradable polyester resin foam sheets and recycled biodegradable polyester resin foam moldings having excellent expansion properties. In particular, the recycled biodegradable polyester resin according to an embodiment of the present invention has a very low melt tension as shown in Table 4, and a person skilled in the art would have conventionally determined that the recycled biodegradable polyester resin according to an embodiment of the present invention would not be able to form a foamed sheet having sufficient foaming properties. However, it has been found that the recycled biodegradable polyester resin according to an embodiment of the present invention can achieve excellent strain hardening properties, and can form a recycled biodegradable polyester resin foamed sheet having excellent foaming properties. [Industrial Applicability]

[0182] The recycled biodegradable polyester resin according to the embodiment of the present invention can be advantageously used in a recycling system for producing a recycled biodegradable polyester resin foam sheet or a recycled biodegradable polyester resin foam molded article having excellent foaming properties. [Explanation of symbols]

[0183] 1 Foam sheet 3 Strand Die 4 Pelletizer 5 Drying equipment 6 Cooling device 10 Tandem Extruder 10a First Extruder 10b Second Extruder 11 Hopper 12 Gas inlet 21 Laura 22 Winding roller 30 Twin screw extruder

Claims

1. A recycled biodegradable polyester resin using a biodegradable polyester resin foam as a recycled raw material, In a graph in which the logarithm of the strain amount ε is plotted on the horizontal axis and the logarithm of the extensional viscosity η (Pa s) is plotted on the vertical axis, the slope a of the graph in the direction from the inflection point toward the direction in which the strain amount increases is 2 is 0.30 (Pa s) or more, Recycled biodegradable polyester resin.

2. The recycled biodegradable polyester resin according to claim 1 , wherein the biodegradable polyester resin foam is produced by melt-kneading a resin composition containing the biodegradable polyester resin in an extruder and extruding and foaming the resin composition.

3. The slope a of the graph 2 (Pa s) and the slope a of the graph in the direction from the inflection point to the direction in which the strain increases in a graph in which the logarithm of the strain amount ε is on the horizontal axis and the logarithm of the extensional viscosity η (Pa s) is on the vertical axis, which are obtained by uniaxial extensional viscosity measurement of the biodegradable polyester resin at 160 ° C. 1 (Pa s) (a 2 / a 1 3. The recycled biodegradable polyester resin according to claim 2, wherein the β-dispersion ratio (β) is 0.10 or more.

4. The recycled biodegradable polyester resin according to claim 2, wherein the biodegradable polyester resin is a polylactic acid resin (P).

5. The recycled biodegradable polyester resin according to claim 4, wherein the polylactic acid resin (P) is a modified polylactic acid resin.

6. The recycled biodegradable polyester resin according to claim 1, wherein the recycled biodegradable polyester resin is obtained by melt-kneading a raw material composition containing the biodegradable polyester resin foam in an extruder, and pelletizing the extruded mixture.

7. The recycled biodegradable polyester resin according to claim 1 , wherein the recycled biodegradable polyester resin is a biodegradable polyester resin foam.

8. The Z-average molecular weight (M Z 2. The recycled biodegradable polyester resin according to claim 1, wherein the molecular weight of the polyester resin is 300,000 or more.

9. The recycled biodegradable polyester resin according to claim 1, wherein the recycled biodegradable polyester resin has an MFR of 15 g / 10 min or less.

10. The recycled biodegradable polyester resin according to claim 1, wherein the recycled biodegradable polyester resin has a melt tension of 1 cN or more at 190°C.

11. A recycled biodegradable polyester resin foam sheet obtained by foaming a recycled resin composition containing the recycled biodegradable polyester resin according to any one of claims 1 to 10.

12. In a graph in which the logarithm of the strain amount ε obtained by uniaxial extensional viscosity measurement at 160°C of the recycled biodegradable polyester resin foam sheet is plotted on the horizontal axis and the logarithm of the extensional viscosity η (Pa s) is plotted on the vertical axis, the slope a of the graph in the direction in which the strain amount increases from the inflection point is 3 The recycled biodegradable polyester resin foam sheet according to claim 11, wherein the viscosity is 0.30 (Pa·s) or more.

13. The recycled biodegradable polyester resin foam sheet according to claim 11, having a thickness of 0.5 mm to 7 mm.

14. Basis weight 50g / m 2 Up to 600 g / m 2 The recycled biodegradable polyester resin foam sheet according to claim 11,

15. The recycled biodegradable polyester resin foam sheet according to claim 11, having an expansion ratio of 4 to 20 times.

16. The recycled biodegradable polyester resin foam sheet according to claim 11, having an open cell ratio of 50% or less.

17. A recycled biodegradable polyester resin foam molded article obtained by molding the recycled biodegradable polyester resin foam sheet according to claim 11.

Citation Information

Patent Citations

  • Method for producing modified polylactic resin, polylactic resin and polylactic resin foam sheet

    JP2019183098A

  • Polylactic acid resin foam

    JP6971947B2